Sensitive determination of buformin using poly-aminobenzoic acid modified glassy carbon electrode - Gui-Ying Jin; Hui Li; Wan-Bang Xu (Elsevier, 2012)
Glassy carbon electrode, which is used to electrochemically determine the content of buformin, is modified with an electropolymerized film of p-aminobenzoic acid in pH 7.0 acetate buffer solution (ABS). The polymer showed an excellent electrocatalytic activity for the reduction of buformin. In pH 7.0 ABS, the cathodic peak current increased linearly over three concentration intervals of buformin, and the detection limit (S/N=3) was 2.0Ã10â9Â g/mL. The method was successfully applied to directly determine buformin in tablets with standard addition recoveries of 95.8â102.5%. The proposed method is simple, cheap and highly efficient. Keywords: Chemically modified electrode, Aminobenzoic acid, Buformin